2018
DOI: 10.1002/nop2.223
|View full text |Cite
|
Sign up to set email alerts
|

Reporting adverse events—Swedish Registered Nurses experience in a municipal home care context

Abstract: Aim To describe how Registered Nurses in a municipal home care context experience adverse event reports. Design A qualitative design was used. Method Twelve semistructured individual interviews with Registered Nurses in a municipal home care context were collected on two occasions and analysed with qualitative content analysis. Results The results show that conflicts exist between being able to trust the managers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, a challenge was also highlighted in this process: when it came to reporting incidents, HVNs recognize the need to report adverse events, but these events are underreported because of shame [ 37 ]. In this study, HVNs experienced stress related to the lack of anonymity in reporting, given that home-visiting nursing agencies are typically small.…”
Section: Discussionmentioning
confidence: 99%
“…However, a challenge was also highlighted in this process: when it came to reporting incidents, HVNs recognize the need to report adverse events, but these events are underreported because of shame [ 37 ]. In this study, HVNs experienced stress related to the lack of anonymity in reporting, given that home-visiting nursing agencies are typically small.…”
Section: Discussionmentioning
confidence: 99%
“…This was regarded as a time consuming and complex task to accomplish, partly because of the negative character of their feedback to the HCAs. This complexity regarding reporting and communicating adverse events in home health care has been highlighted in a prior study demonstrating that reporting of adverse events that involve colleagues is considered distressing by nurses [ 47 ]. The eMAR used in this study allowed nurses to observe inaccuracies in delegated tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, if procedures are not strictly followed, it is more likely that preventable adverse events will occur (Henriksen et al, 2009). Considering the homecare environment and working conditions, it has been reported that professionals do not feel confident with new procedures (Pejner & Kihlgren, 2019). Strong safety management is also needed in long‐term professional homecare.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the homecare environment and working conditions, it has been reported that professionals do not feel confident with new procedures (Pejner & Kihlgren, 2019). Strong safety management is also needed in long-term professional homecare.…”
Section: Discussionmentioning
confidence: 99%